2013
DOI: 10.1111/all.12210
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy for Hymenoptera venom allergy: too expensive for European health care?

Abstract: We read with interest the commentary by Ru€ eff et al. (1) regarding our health economic appraisal of Pharmalgen â wasp and bee venom immunotherapy (VIT) for the National Institute for Health and Care Excellence (NICE) (2). We are grateful to the authors for highlighting the surprising results of our analysis to the European allergy community and would like to respond to the critique of our approach.Our main finding was that VIT is not considered to be cost-effective, when only the direct costs of fatal and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Indeed, in times of spending review also the cost-effectiveness of VIT is questioned [ 21 ]. Nobody can argue its life-saving role when the culprit venom is used, but avoiding additional treatments with unnecessary venoms, as obtained by CAP-inhibition, that in our study spared 30 additional treatments in 54 patients, may allow to significantly reduce the costs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in times of spending review also the cost-effectiveness of VIT is questioned [ 21 ]. Nobody can argue its life-saving role when the culprit venom is used, but avoiding additional treatments with unnecessary venoms, as obtained by CAP-inhibition, that in our study spared 30 additional treatments in 54 patients, may allow to significantly reduce the costs.…”
Section: Discussionmentioning
confidence: 99%
“…A health economic analysis undertaken for the UK National Institute for Health and Care Excellence found that a highly effective treatment for venom allergy, subcutaneous venom immunotherapy, was only cost effective if quality of life improvement occurred, or in specific high-risk groups with frequent stings and frequent reactions, such as beekeepers. 72 , 73 , 74 This was due to the rarity of costly outcomes such as death or disability in patients with known venom allergy. Disability is not widely reported as an outcome of venom anaphylaxis, but anecdotal evidence suggests that persistent vegetative state after hypoxic encephalopathy in near-fatal venom anaphylaxis is a significant risk, and this may impact on health economic analyses.…”
Section: Fatal Venom Anaphylaxismentioning
confidence: 99%
“…In general, they found that VIT is not cost-effective when only considering direct costs of outcomes. 87 This is because for most people, recurrent insect stings are rare, and even in those with a history of severe venom allergic reaction previously, the risk of fatal outcome following a sting is extremely low. However, immunotherapy was found to be cost-effective in patients at high risk of future stings (≥3.3 a year, for people such as bee keepers, their neighbors and children, roofers, and gardeners) and in those whom the quality of life indices show improvement with reduced anxiety.…”
Section: Cost-effectiveness Of Vitmentioning
confidence: 99%